Amyloid precursor protein maintains constitutive and adaptive plasticity of dendritic spines in adult brain by regulating D-serine homeostasis - Zou, Chengyu; Müller, Ulrike C. (The EMBO journal, 2016)
Dynamic synapses facilitate activity-dependent remodeling of neural circuits, thereby providing the structural substrate for adaptive behaviors. However, the mechanisms governing dynamic synapses in adult brain are still largely unknown. Here, we demonstrate that in the cortex of adult amyloid precursor protein knockout (APP-KO) mice, spine formation and elimination were both reduced while overall spine density remained unaltered. When housed under environmental enrichment, APP-KO mice failed to respond with an increase in spine density. Spine morphology was also altered in the absence of APP. The underlying mechanism of these spine abnormalities in APP-KO mice was ascribed to an impairment in D-serine homeostasis. Extracellular D-serine concentration was significantly reduced in APP-KO mice, coupled with an increase of total D-serine. Strikingly, chronic treatment with exogenous D-serine normalized D-serine homeostasis and restored the deficits of spine dynamics, adaptive plasticity, and morphology in APP-KO mice. The cognitive deficit observed in APP-KO mice was also rescued by D-serine treatment. These data suggest that APP regulates homeostasis of D-serine, thereby maintaining the constitutive and adaptive plasticity of dendritic spines in adult brain.